2018
DOI: 10.14701/ahbps.2018.22.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Clinical patterns of postcholecystectomy syndrome

Abstract: Backgrounds/AimsPostcholecystectomy syndrome represents a heterogeneous group of symptoms and findings in patients who have previously undergone cholecystectomy. It is rare and under-reported in Saudi Arabia. It can be attributed to many complications such as bile duct injury, biliary leak, retained common bile duct stones, recurrent bile duct stones, and bile duct strictures. In this study, we aimed to analyze the causes and evaluate the approach to postcholecystectomy syndrome in our local Saudi Arabian comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 14 publications
1
46
1
1
Order By: Relevance
“…Most striking feature of that study is that they found helicobacter pylori infection is the second most common cause for post-cholecystectomy syndrome while in our study we did not find such cause in patients. 22…”
Section: Discussionmentioning
confidence: 99%
“…Most striking feature of that study is that they found helicobacter pylori infection is the second most common cause for post-cholecystectomy syndrome while in our study we did not find such cause in patients. 22…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Gender-specific risk factors may contribute to the development of these symptoms. 10 Biliary factors include choledocholithiasis, biliary stricture, and sphincter of Oddi dysfunction. 5,6 Nonbiliary factors include pancreatic disorders, peptic ulcer, liver disease, irritable bowel syndrome, coronary artery disease, and gastroesophageal reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Among cases of late PCS, remnant stones in cystic duct stump account for 17%–25% cases 6. A cystic duct stump >1 cm in length after cholecystectomy causing PCS is known as cystic duct stump syndrome 7. Palanivelu et al 8 reported an incidence of remnant cystic duct calculus of 4.19% in LC as compared with 0.02% in open cholecystectomy 9…”
Section: Discussionmentioning
confidence: 99%